Movement of sediment in the nearshore zone, Gibraltar Point, Lincolnshire - Dugdale, Robert Edward (1977)
A descriptive sediment movement model has been created for an area of the nearshore zone near Gibraltar Point, Lincolnshire on the basis of evidence from studies of sediments, sandbank and channel morphology, bedforms, tidal currents and sediment tracer experiments. The area is subject to linear tidal currents which have created a system of tidal current ridges, tidal channels and an ebb-tidal delta. Sediment movement associated with these sandbanks and channels was found to have a net northerly drift related to an ebb tidal residual in the Boston Deep, the largest channel in the area. Sediment circulation around the sandbank system was considered to be essentially closed with a large sediment storage element represented by the sandbanks. An area of the foreshore was identified as a possible location for movement of sediment from the nearshore zone to the foreshore zone.